Inovasi Media Edukasi Flashcard “Care For Teen” Sebagai Upaya Peningkatan Pengetahuan HIV/AIDS Pada Siswa SMAN 1 Ungaran - Luhurningtyas, Fania Putri; Oktianti, Dian; Aprilliana R, Melati (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2020)
Indonesia ranks third as the region with the highest number of HIV / AIDS sufferers in the world with 5.2 million people. The prevalence of HIV / AIDS sufferers mostly starts with the youth group. Quitting drugs begins with smoking, then stripping drugs. Behavior related to adolescents, this age is a period of self-discovery. The curious nature of adolescents must be facilitated with correct and correct information media, including information on HIV / AIDS. Providing appropriate information and making a conducive environment can help teenagers as potential future generations of the nation to make good decisions. The influence of the development of information and communication technology also affects the learning process to create millennials. On average, Indonesian teenagers already know and use the internet in their daily lives. However, most of them have not been able to distinguish between positive and negative sources from the internet, and tend to be easily used by their social environment. It needs attractive and practical methods to increase knowledge about HIV / AIDS in youth group. The target of this community service program is students of Senior High School 01Ungaran, Semarang Regency. The educational method is the Make a Match cooperative method. It used flashcards that contain information on HIV / AIDS and the risk of transmission. Another goal of service that was achieved was the attitude of the participants towards people living with HIV / AIDS (PLWHA). The community service stage consists of making flashcards for HIV / AIDS education and evaluation. The 30 students were very enthusiastic. Students are actively involved in discussion sessions. After being given the material presented, the students' knowledge about HIV / AIDS was increased before and after presenting the educational material. Abstrak Indonesia menduduki peringkat ketiga sebagai wilayah dengan pengidap HIV/AIDS terbanyak di seluruh dunia sebanyak 5,2 juta jiwa. Prevalensi penderita HIV/AIDS paling banyak diawali dari kelompok remaja. Umumnya penyalahgunaan narkoba diawali dengan merokok, kemudian berlanjut penyalahgunaan narkoba. Perilaku beresiko tersebut berhubungan dengan remaja, dimasa usia tersebut adalah masa pencarian jati diri. Sifat remaja yang ingin tahu tersebut harus difasilitasi dengan media informasi yang baik dan benar, termasuk informasi penyakit HIV/AIDS. Pemberian informasi yang sesuai dan pembentukan lingkungan yang kondusif dapat membantu remaja sebagai calon generasi penerus bangsa dapat mengambil keputusan yang baik. Pengaruh perkembangan teknologi informasi dan komunikasi juga mempengaruhi proses pembelajaran generasi milenial. Rata “ rata di antara kalangan remaja Indonesia telah mengenal dan menggunakan internet dalam keseharian mereka. Namun kebanyakan dari mereka belum mampu untuk memilah antara aktivitas internet yang bersifat positif dan negatif, serta cenderung mudah terpengaruh oleh lingkungan sosial mereka dalam penggunaannya. Perlunya metode menarik dan praktis untuk meningkatkan pengetahuan tentang HIV/AIDS pada remaja. Sasaran program pengabdian masyarakat ini adalah pelajar SMA N 1 Ungaran, Kabupaten Semarang. Metode edukasi dilakukan metode kooperatif Make a Match menggunakan flash card berisikan informasi HIV/AIDS dan resiko penularannya. Tujuan pengabdian lainnya yang hendak dicapai yaitu sikap peserta terhadap Orang Dengan HIV/AIDS(ODHA). Tahapan pengabdian terdiri dari pembuatan media flash card, edukasi HIV/AIDS, dan evaluasi. Peserta yang mengikuti sebanyak 30 siswa sangat antusias. Siswa terlibat aktif dalam sesi diskusi. Setelah diberikan pemaparan materi, terdapat peningkatan pengetahuan siswa tentang HIV/AIDS antara sebelum dan sesudah pemberian materi edukasi.